Cell-type specific distribution and activation of type I IFN pathway molecules at the placental maternal-fetal interface in response to COVID-19 infection - Wang, Yuping; Gu, Yang; Lewis, David F.; Gu, Xin; Brown, Karisa; Lachute, Courtney; Hankins, Miriam; Scott, Rona S.; Busada, Caitlin; Cooper, Danielle B.; McCathran, Charles E.; Barrilleaux, Perry (Frontiers in Endocrinology, 2023)
Background and Objective: COVID-19 infection in pregnancy significantly increases risks of adverse pregnancy outcomes. However, little is known how the innate immunity at the placental maternal-fetal interface responds to COVID-19 infection. Type I IFN cytokines are recognized as a key component of the innate immune response against viral infection. In this study, we specifically evaluated expression of IFN antiviral signaling molecules in placentas from women infected with COVID-19 during pregnancy. Methods: Expression of IFN activation signaling pathway molecules, including stimulator of interferon genes (STING), cyclic GMP–AMP synthase (cGAS), interferon regulatory factor 3 (IRF3), mitochondrial antiviral-signaling protein (MAVS), Toll-like receptor 7 (TLR7), and IFN, was determined in formalin-fixed paraffin imbedded (FFPE) placental tissue sections by immunostaining. A total of 20 placentas were examined, 12 from COVID-19 patients and 8 from non-COVID controls. Patient demographics, clinical data, and placental pathology report were acquired via EPIC medical record review. Results: Other than BMI, there was no statistical difference between COVID and non-COVID groups in maternal age, gestational age at delivery, gravity/parity, racial status, delivery mode, and newborn gender and weight. In COVID-exposed placentas, the main pathological characteristics in the placental disc are maternal and fetal vascular malperfusion and chronic inflammation. Compared to non-COVID controls, expression of IFN activation pathway molecules were all upregulated with distinct cell-type specific distribution in COVID-exposed placentas: STING in villous and decidual stromal cells; IRF3 in cytotrophoblasts (CTs) and extravillous trophoblasts (EVTs); and MAVS and TLR7 in STCs, CTs, and EVTs. Upregulation of MAVS and TLR7 was also seen in fetal vessel endothelial cells. Conclusions: STING, IRF3, MAVS, and TLR7 are key viral sensing molecules that regulate Type I IFN production. Type I IFNs are potent antiviral cytokines to impair and eradicate viral replication in infected cells. The finding of cell-type specific distribution and activation of these innate antiviral molecules at the placental maternal-fetal interface provide plausible evidence that type I IFN pathway molecules may play critical roles against SARS-CoV-2 infection in the placenta. Our findings also suggest that placental maternal-fetal interface has a well-defined antiviral defense system to protect the developing fetus from SARS-CoV-2 infection.